Racism in German healthcare: uncovering the construction and silencing of the “other” - Tanja Gangarova; Melike Yildiz; Lina Kabangu (Frontiers in Public Health)
While the impact of racism on healthcare interactions has been researched extensively in many parts of the world, substantive studies on healthcare-related racism in Europe, and particularly in Germany, remain scarce. This paper builds on a study that applies Community-Based Participatory Research (CBPR) and aims to explore healthcare users’ experiences of racism within German healthcare. Community members were trained as peer researchers and given support as they conducted a total of six focus group discussions that involved a total of 14 study participants: these participants were organized into two subsamples of seven participants each (subsample one: Black, African, Afro-diasporic healthcare users; subsample two: healthcare users perceived or self-describing as Muslim), and each subsample had three focus group discussions. A democratic approach to qualitative data analysis was applied in the form of the DEPICT model. The data analysis developed iteratively, with inductive and deductive steps complementing one another. The study results illustrate how the collaboratively developed concepts of being treated as “other” and being made inaudible can advance our understanding of the forms, dynamics, and effects of racism in healthcare encounters. Because this paper focuses on the process of racialization, it helps illumine the mechanisms of subtle racism, which, as study results suggest, can damage healthcare users, cause a loss of trust in the system, and lead to invisibilization of racism in healthcare. By doing so, it draws attention to areas for change and transformation, to larger power structures that must be challenged in order to ensure responsive and equal healthcare for all healthcare users. The application of CBPR and, particularly, the engagement of racialized healthcare users in the research process offered pathways for analyzing the subtle, otherwise hard-to-detect mechanisms of racism, and for learning from the wisdom of situated knowledges.